Antioxidant activity and protective effect against oxidative hemolysis of Azadirachta indica A. Juss / Norhisham Haron ... [et al.] - Haron, Norhisham; Wan Marno, Wan Muhammad Izzuddin; Mohamed, Emida; Camalxaman, Siti Nazrina; Rambely, Azlin Sham (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Toxic effects of free radical on various diseases have been reported. Increased oxidative stress level in cells led to severe damage to nucleic acid, lipids and proteins. Erythrocytes are highly susceptible to oxidative damage which implicate to hemolysis. Azadirachta indica (AI) is widely used as traditional medicine for remedy against many injuries. The present study was to investigate the antioxidant activity and protective effect of AI leaves extract against hydrogen peroxide induced hemolysis. Antioxidant activities of ethanolic extract of AI were determined by free radical (1, 1-diphenyl-2-picrylhydrazyl; DPPH and nitric oxide) scavenging activity and ferric reducing antioxidant power (FRAP). The protective effect of AI against hemolysis in hydrogen peroxide (H2O2) induced erythrocytes was also investigated. The extract was found to scavenge DPPH and nitric oxide with the IC50 of 680.20 ± 4.51 μg/ml and 636.0 ± 14.71 μg/ml, respectively. The reducing power value shown 47 mg of ascorbic acid is equivalent to one gram of AI extract. The extract demonstrated protection to erythrocytes against oxidative hemolysis with an IC50 of 415.56 ± 11.05 μg/ml. In conclusion, the AI leaves extract had an antihemolytic activity which mediated by its antioxidant properties.